Malem Songo Marriage in a Cultural Islamic Framework: Acculturation of Islam and Local Traditions of the Coastal Community of Tuban - Aizatul Ulla; Nur Khofifatun Nisah; Rida Ayu Agustina; Nurul Hakim (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
This study aims to analyze the tradition of Malem Songo Marriage within the framework of cultural Islam as a form of acculturation between Islamic teachings and local traditions of the coastal community in Tuban. This research employs an empirical normative method with case and historical approaches, using interviews, observations, and literature studies for data collection. The results show that the Malem Songo Marriage tradition is a marriage practice conducted on the 29th night of Ramadan and has been passed down through generations. This tradition reflects a harmonious acculturation process between Islamic values and local culture, where its implementation still fulfills the pillars and requirements of a valid marriage in Islam. From the perspective of Islamic law and state law, this practice is considered legitimate as long as it is not accompanied by absolute beliefs regarding certain times determining the success of marriage. In addition, this tradition also holds religious, social, and economic values, such as strengthening social solidarity and reducing wedding costs. Therefore, Malem Songo Marriage can be understood as a form of cultural Islam that is adaptive without deviating from Islamic principles.